Fitness, motor competence and body composition as correlates of adolescent neck/shoulder pain: an exploratory cross-sectional study - O'Sullivan Peter B; Straker Leon M; Perry Mark C; Smith Anne J; Hands Beth (BMC, 2008)
Abstract Background Adolescent neck/shoulder pain (NSP) is a common and sometimes debilitating problem. Several risk factors for this condition have been investigated, but no studies have previously evaluated associations between fitness, motor competence, body composition and adolescent NSP. Methods 1608 males and females of mean age 14 years answered questions on their history of NSP (4 measures), and were tested for aerobic fitness, upper and lower limb power, trunk endurance, grip strength, shoulder flexibility, motor competence and anthropometric factors. Univariate and multivariate logistic regressions were used to test for associations between NSP and physical variables. Results There were significant gender differences for most physical and pain variables. After multivariate analysis, males had lower odds of NSP if they had reduced back endurance [OR: 0.66 (95% CI: 0.46-0.97)], reduced persistent control [0.42 (0.19-0.95], and increased muscle power [0.33 (0.12-0.94)], and higher odds of NSP if they had a higher basketball throw [2.47 (1.22-5.00)] and jump performance [3.47 (1.55-7.74)]. Females had lower odds for NSP if they had a reduced jump performance [0.61(0.41-0.92)], a better basketball throw [0.60(0.40-0.90)], lower shoulder flexibility [0.54 (0.30-0.98)] and a higher aerobic capacity [0.61 (0.40-0.93)], and higher odds for NSP if they had greater abdominal endurance [1.57(1.07-2.31)] and greater bimanual dexterity [1.77(1.18-2.65)]. Females showed a U shaped relationship between NSP and back endurance [low: 2.12 (1.20-3.74); high 2.12 (1.18-3.83)]. Conclusion Adolescent NSP was associated with fitness and motor competence, although the associations varied with gender, and their strength was limited.